Kesediaan Sekolah-sekolah Agama Islam di Selatan Thailand dalam melaksanakan jaminan kualiti pendidikan daripada aspek proses - Supyan Hussein, (penerbit ukm, 2007)
This article explains the implementation of a legislative policy in Thailand which impose that all education institutions, including the private Islamic religious schools to improve the quality of education in various aspects especially the process of management, communication and learning. The process of quality assurance in Thailand follows the Oakland Model which was modified according to the education needs of Thailand and the International Standard of Quality (ISO). Sample for this study was taken from 393 quality assurance committee members of 120 private Islamic religious schools. The questionnaire was developed based on the goverment’s formal quality assurance document. Respondents were asked to assess and evaluate the level of schools’ readiness in the aspects of the standard management process. In general the study reveals that the readiness of the schools is at the average and satisfactory level despite experiencing problems and limitations.